Childfree Dalam Pernikahan Perspektif Maqoshid Syariah - Fatmawati Fatmawati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
The presence of children in a marriage is one of the means of achieving happiness that is longed for by descendants, sometimes life in the family feels bland. The presence of married couples in general. For married couples who don't have children, it actually gives their own color to a family. It's just that recently the world of cyberspace has been stirred up by the term Childfree, even on several social media in Indonesia, on Twitter, Instagram, Facebook, YouTube and other online media platforms, it has become a trending topic of discussion in digital society. Childfree is an agreement made by a husband and wife not to have children for various reasons. This research aims to examine and consider the factors that motivate someone to choose childfree using the maqoshid al-syari'ah approach so that it can be a guide for placing a level of urgency on the choice of childfree in a family.